Anisotropic Weak Hardy Spaces and Wavelets - B. Barrios; J. J. Betancor (Journal of Function Spaces and Applications)
We characterize the anisotropic weak Hardy spaces HAp,∞(ℝn) associated with an expansive matrix A by using square functions involving wavelets coefficients.